1986
DOI: 10.1366/0003702864509493
|View full text |Cite
|
Sign up to set email alerts
|

The UV Absorption Spectra of Chemical Agents and Simulants

Abstract: The uv spectra of chemical agents GA, GB, GD, VX, HD, and L and common agent simulants have been measured in cyclohexane solution from 350 to 200 nm. The purity of the agents, measured by gas chromatographic analysis, was in general >96%. At 230 nm, the strength of the uv absorption followed the general trend L > VX > GA > HD > GD > GB > DMMP. Except for HD and L, agent spectra lacked characteristic features that will be useful for remote detection by uv sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 7 publications
5
9
0
Order By: Relevance
“…Measurement ol the ultraviolet absorption spectrum of the sample in isooctane revealed that the spectrum and the absorptivity of the material at 215 nm agreed with published values in the literature (Rewick, et al, 1986;Mohler and Sorge, 1939) and did not indicate the presence of ultravioletbsorbing compounds other than Lewisite. This conclusion was supported by our results from gas-chromatographic analyses of the sample following derivatization with 2-mercaptoethanol.…”
Section: Lewisitesupporting
confidence: 81%
“…Measurement ol the ultraviolet absorption spectrum of the sample in isooctane revealed that the spectrum and the absorptivity of the material at 215 nm agreed with published values in the literature (Rewick, et al, 1986;Mohler and Sorge, 1939) and did not indicate the presence of ultravioletbsorbing compounds other than Lewisite. This conclusion was supported by our results from gas-chromatographic analyses of the sample following derivatization with 2-mercaptoethanol.…”
Section: Lewisitesupporting
confidence: 81%
“…Measurement of the ultraviolet absorption spectrum of the sample in isooctane revealed that the spectrum and the absorptivity of the material at 215 nm agreed with published values in the literature (Rewick, et al, 1986;Mohler and Sorge, 1939) and did not indicate the presence of ultraviolet-absorbing compounds other than lewisite. This conclusion was supported by results from gas-chromatographic analyses of the sample following derivatization with 2-mercaptoethanol (Appendix A).…”
Section: Subcutaneoussupporting
confidence: 81%
“…[1,2,9,[11][12][13][14][15][16][17] Previous experimental and theoretical studies on OPs containing AOCH 3 or AOCH 2 A reported that reactions of these OPs with O 2 /NO result in the formation of an alkoxy radical ([P(O)OCH(OÁ)A). [12,15,[18][19][20][21][22] These results are in agreement with a subsequent rearrangement of the alkoxy radical occurring through a five-member transition state with the formation of [P(O)OH and a molecular carbonyl radical. In a recent experimental study, [23] the rate constant for atmospheric reaction of OH radicals and a simulant OP containing the AOCH\ and AOCH 3 groups isopropyl methyl methylphosphonate (IMMP, (CH 3 ) 2 CHO-P(O)(CH 3 )OCH 3 ) was determined to be 6.72 Â 10 À11 cm 3 mol À1 s…”
Section: Introductionsupporting
confidence: 75%